Trostbedürftig und hassgefährdet: Religiosität in Zeiten globaler Krisen - Welker, Michael (Evangelische Theologie, 2021)
The article shows that severe global crises, such as we are currently experiencing, threaten not only natural and mental life, but also spiritual life. Self-confidence, trust in the world and trust in God are shaken. For theology and the churches, self-examination and self-criticism should be the first priority in this situation. Long-held misconceptions of God and God's omnipotence and nature-romantic notions of creation urgently need to be corrected. Constructively, the powers of the divine Spirit, a spirit of justice, freedom, truth, peace and human kindness should be recognized, appreciated and strengthened. This Spirit gives multiform comfort and counteracts the dangers of the spread of a multifaceted hatred. The danger of hatred not only in its loud and aggressive forms, but also in the quieter forms of increasing unkindness and decreasing trust in God, paralyzing resignation and indifference, is counteracted by the Spirit of comfort in an overwhelming way. It surrounds us from all sides, not only in family, friendship, therapeutic and pastoral relationships. As a Spirit of practiced justice, freedom, truth and peace, it is a worldwide source of reassurance, security, confidence, courage and new hope.
Gesehen am 09.07.2021
Keywords: Nächstenliebe; Gott; Pandemie; COVID-19